Publisher Correction: Studying light-harvesting models with superconducting circuits - Anton Potočnik; Arno Bargerbos; Florian A. Y. N. Schröder; Saeed A. Khan; Michele C. Collodo; Simone Gasparinetti; Yves Salathé; Celestino Creatore; Christopher Eichler; Hakan E. Türeci; Alex W. Chin; Andreas Wallraff (Nature Communications, 2018)
The original HTML version of this Article contained an error in the second mathematical expression in the fourth sentence of the fourth paragraph of the ‘Excitation transfer with uniform white noise’ section of the Results. This has been corrected in the HTML version of the Article. The original PDF version of this Article incorrectly stated that ‘Correspondence and requests for materials should be addressed to A. Pčn.’, instead of the correct ‘Correspondence and requests for materials should be addressed to A. Potočnik’. This has been corrected in the PDF version of the Article.